2019
DOI: 10.3390/ijms20225523
|View full text |Cite
|
Sign up to set email alerts
|

Broad-Spectrum Disease Resistance Conferred by the Overexpression of Rice RLCK BSR1 Results from an Enhanced Immune Response to Multiple MAMPs

Abstract: Plants activate their immune system through intracellular signaling pathways after perceiving microbe-associated molecular patterns (MAMPs). Receptor-like cytoplasmic kinases mediate the intracellular signaling downstream of pattern-recognition receptors. BROAD-SPECTRUM RESISTANCE 1 (BSR1), a rice (Oryza sativa) receptor-like cytoplasmic kinase subfamily-VII protein, contributes to chitin-triggered immune responses. It is valuable for agriculture because its overexpression confers strong disease resistance to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…Transcriptional activation of defense-related genes was assessed by quantitative reverse-transcription (RT-q)PCR. PROBENAZOLE-INDUCIBLE PROTEIN 1 ( PBZ1 ) and KAURENE SYNTHASE-LIKE 4 ( KSL4 ), the expression of which is upregulated in response to chitin [ 12 ], were analyzed. Chitin treatment remarkably increased PBZ1 and KSL4 transcript levels in BSR1 ox6 leaf strips, but not in OsCERK1 ko: BSR1 ox#4-4 and #10-2 leaf strips ( Figure 2 b).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Transcriptional activation of defense-related genes was assessed by quantitative reverse-transcription (RT-q)PCR. PROBENAZOLE-INDUCIBLE PROTEIN 1 ( PBZ1 ) and KAURENE SYNTHASE-LIKE 4 ( KSL4 ), the expression of which is upregulated in response to chitin [ 12 ], were analyzed. Chitin treatment remarkably increased PBZ1 and KSL4 transcript levels in BSR1 ox6 leaf strips, but not in OsCERK1 ko: BSR1 ox#4-4 and #10-2 leaf strips ( Figure 2 b).…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of BSR1 enhances disease resistance [ 6 , 7 ]. In a previously suggested model, the underlying mechanism was as follows: intracellular signaling following MAMP-recognition would be amplified via overaccumulation of BSR1, resulting in enhanced broad-spectrum immunity [ 12 ]. The simultaneous overexpression and knockout experiment in our study revealed that the enhancement of resistance depends on OsCERK1 ( Figure S4 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, there are many studies investigating the molecular mechanisms of rice immune responses, such as receptor-mediated pathogen recognition, host immune signaling, and pathogen effector-mediated susceptibility. In this Special Issue, Kanda et al focuses on the BSR1 gene, which encodes a receptor-like cytoplasmic kinase subfamily VII protein and concludes that the hyperactivation of microbe-associated molecular pattern (MAMP)-triggered immune responses conferred robust BSR1 -mediated broad spectrum resistance to fungal and bacterial pathogens [ 17 ]. Liu et al reports that the OsAAA-ATPase1 gene enhanced the expression of pathogenesis-related genes, salicylic acid (SA)-mediated defense responses, and resistance to rice blast fungus [ 18 ].…”
mentioning
confidence: 99%